PENGARUH BIAYA KUALITAS TERHADAP PROFITABILITAS PERUSAHAAN (studi kasus pada industri manufaktur di Bursa Efek Indonesia Tahun 2018-2023) - Diah Aliffia Hanifa; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of quality costs on profitability in the manufacturing industry listed in the Indonesia Stock Exchange (IDX). This research data uses secondary data obtained from the company's annual report in the 2018-2023 period. The method used is multiple linear analysis using the IBM SPSS Statistic 25 application.The results of this study indicate that partially prevention costs have no negative effect on Return on Asset and no positive effect on Return on Equity, appraisal costs have a positive and significant effect on Return on Assets but no effect on Return on Equity, internal failure costs have a positive and significant effect on Return on Asset and Return on Equity, external failure costs have a significant negative effect on Return on Asset and Return on Equity. Quality costs consisting of prevention costs, assessment costs, internal failure costs and external failure costs have a significant positive effect on Return on Asset and Return on Equity.Thus, the results of this study emphasize the importance of effective quality management, especially in suppressing external failures and managing quality costs strategically to increase company profitability. It is hoped that these findings can be input for company management in making decisions regarding the allocation of quality costs and become a reference for further research in the field of accounting